From Battered Wives to Domestic Violence: The Transnational Circulation of Chiswick Women's Aid and Erin Pizzey's Scream Quietly or the Neighbours Will Hear (1974). Issue 2 (2nd April 2020) - Simic, Zora
Abstract : The transnational influence of Chiswick Women's Aid and their community house, considered the first feminist refuge, as well as that of its founder, Erin Pizzey, author of the 1974 international best-seller Scream Quietly or the Neighbours Will Hear, has been widely noted. Yet despite such acknowledgements, their formative influence remains largely unexamined. Without overstating their significance, I pursue here a more thorough examination of their impact, in order to consider both the shared and specific features of feminist mobilisations around what came to be known as domestic violence in the United Kingdom, United States and Australia. A transnational approach reveals how Pizzey and Chiswick inaugurated the feminist refuge movement and seeded a feminist critique of domestic violence, but that there were variations and limits to this foundational influence. Accordingly, Pizzey and Chiswick are freshly interpreted as part of a wider, multi-faceted and evolving feminist response to domestic violence.